PENGARUH PARTISIPASI DALAM PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KEADILAN PROSEDURAL, BUDAYA PATERNALISTIK, MOTIVASI DAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI PADA SATUAN KERJA PERANGKAT DAERAH DI PROVINSI RIAU - Tesi Pratiwi; Taufeni Taufik; Restu Agusti (Program Studi Pendidikan Ekonomi Universitas Riau, 2017)
This research was conducted at regional governance institution of Riau Province.The objectives to be achieved in this research is to know the influence ofparticipation of budget preparation, participation of budget preparation moderated byprocedural justice, participation of budget preparation moderated by paternalisticculture, participation of budget preparation moderated by motivation andparticipation of budget preparation moderated by organizational commitment to themanagerial performance in regional governance institustion of Riau Province. Thepopulation in this study is all agencies in Riau Province Government, which amountsto 51 units. By taking samples using purposive sampling method, that is managerialwho do planning, coordinating, evaluation, supervision, election of staff, negotiationand representation so that obtained as many as 177 sample. To analyse the data isusing Moderated Regression Analysis (MRA). Based on the results obtained, theconclusion can be drawn as follows: participation of budget preparation, proceduralfairness, paternal culture and organizational commitment have a significant influenceon the relationship of budgetary participation and managerial performance inregional governance institustion of Riau Province. While the motivation does nothave a significant influence on the relationship of participation budgeting andmanagerial performance in regional governance institustion of Riau Province.